The Concepts of Nosarara Nosabatutu in the Kaili Community : Inspiration for Religious Harmony in Indonesia - Dwi Septiwiharti; Septiana Dwiputri Maharani; Rizal Mustansyir (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2019)
This article aims to describe the local wisdom and values of Nosarara Nosabatutu in the Kaili community in Central Sulawesi using an axiological perspective as an inspiration for religious harmony in Indonesia. This research employs a qualitative method in the field of philosophical axiology. The object of research material is the teaching of nosarara nosabatutu, and the formal object is the theory of objectivism of values. The analysis shows that family values are at the vital value level, while the value of unity is at the spiritual value level in the Schelerian hierarchy. Both values indicate spiritual sentiments and spiritual preferences. Nosarara teaches individuals to love others as their brothers, as reflected Kaili’s term of sararata le or sararata ia which means s/he is a family. Spiritual nosabatutu teaches one to take care of the family property as shared wealth and also keep other people's secrets because everyone in the Kaili ethnic group comes from the same womb and lives from the same treasure as a family.